Analisis Kebutuhan Pengembangan Metode Eksperimen Terintegrasi Video Animasi pada Materi Perubahan Wujud Benda di Kelas IV SD - Nurafdila, Tiara Rizqy; Nasrulloh, Iman; Purwanti, Yuniar (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2026)
This study aims to analyze the needs for developing an experimental method integrated with animated videos on the topic of changes in the state of matter in Natural and Social Science (IPAS) learning at the elementary school level. The research employed a descriptive qualitative approach with participants consisting of one teacher and fourth-grade students at SDN 4 Sukakarya, Garut Regency. Data were collected through observation, interviews, and questionnaires to identify students’ needs, interests, and learning experiences in IPAS learning. The collected data were analyzed using a qualitative descriptive analysis technique through the stages of data reduction, data presentation, and conclusion drawing. The results showed that IPAS learning was still dominated by lectures and the use of textbooks, causing students to be less active and experience difficulties in understanding abstract concepts. The analysis also indicated that students had a high interest in experimental activities and the use of animated video media as learning support. Therefore, it is necessary to develop an experimental method integrated with animated videos to create more interactive, concrete, and engaging IPAS learning that suits the characteristics of elementary school students.